Implementasi PK Best Learning berbasis Website pada pembelajaran Tarikh di SMA Muhammadiyah Program Khusus Kottabarat - Muhammad Ikhsan Kurnia Putra; Hafidz Hafidz; Syahda Luthfiah Imani; Fahdilla Astri Nur Hidayah; Gangga Bagus Darmawan (At Turots: Jurnal Pendidikan Islam, 2023)
PK Best Learning is one of the innovative learning media that directs students to apply technology in their learning process. The effective implementation of e-learning in educational activities can enhance students' learning outcomes, participation, and concentration. The objective of this research is to examine the implementation and challenges in using website-based e-learning PK Best Learning in the Tarikh subject of the class XI Social at Muhammadiyah High School Kottabarat Special Program. This study employed a descriptive qualitative research design with a case study approach. The data sources used in this research were primary and secondary data. Data were collected through observation, interviews, and documentation study techniques. The data were then validated using triangulation and analyzed descriptively. The findings indicate that PK Best Learning greatly supports educational purposes by providing an e-learning platform that manages the entire academic process of students. Learning through e-learning can be conducted flexibly, anytime and anywhere. PK Best Learning enables flexible implementation of learning, adaptable to the needs and characteristics of students in understanding and exploring the subject matter. In conclusion, the website-based implementation of e-learning PK Best Learning in the Tarikh subject of the class XI Social at Muhammadiyah High School Kottabarat Special Program has been successful in enhancing student engagement in learning, providing significant time efficiency for teachers, and yielding positive impacts such as developing non-academic competencies, learning flexibility, access to diverse learning resources, and the use of interactive learning media. The challenges faced in the implementation of e-learning PK Best Learning include limited technological infrastructure, lack of social interaction, limitations in practical learning, and maintaining motivation and concentration during independent learning.